I Speak for Myself - Hussein Rashid (International Institute of Islamic Thought, 2012)
The anthology, I Speak for Myself, is the first in a series of books that allow Muslims to write about themselves. This volume is about American women describing their experiences of being a Muslima ‒ with one from a man, and further volumes in the series will focus on the American Muslim male perspective and voices from the Arab Spring. Like most anthologies, the submissions are uneven, and with forty essays, there are more than a few poor essays. The editors indicate that they wanted the authors to write essays that reflected their comfortable relationship to country and faith, but otherwise they left the theme open. Although the editors seem to have hoped for a diverse outpouring of essays, and there is a great deal of diversity, there are certain common themes. Most notably were a series of essays by women who only talked about the hijab, as though that was their identity. These essays were fairly similar to one another, which may be the result of the short length of these pieces. There is value in keeping the contributions brief, as stories move along and ideas develop quickly, but is a problem when several people write on the same issue. Despite this general criticism, this book is a natural fit for any course on Islam in America, gender and religion, or even as an introduction to Islam course. There are some absolutely delightful and fascinating essays in this collection. The strongest ones dealt with the implicit nature of being Muslim and American. Rather than discussing either or both identifications, authors simply talked about their lives. Following are several examples of these types of essays ...